2010
DOI: 10.1111/j.1469-7610.2010.02220.x
|View full text |Cite
|
Sign up to set email alerts
|

Mother–child dyadic synchrony is associated with better functioning in hyperactive/inattentive preschool children

Abstract: Dyadic synchrony between mother and child plays a role in the functioning of preschool children displaying elevated symptoms of hyperactivity/inattention, and may represent a potential area for intervention that is not generally addressed in most parent management training programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 48 publications
0
43
0
1
Order By: Relevance
“…The procedure for data collection for this study has been described elsewhere (Healey, Gopin, Grossman, Campbell, & Halperin, 2010) and therefore will only be briefly described here. Data were collected in two phases.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure for data collection for this study has been described elsewhere (Healey, Gopin, Grossman, Campbell, & Halperin, 2010) and therefore will only be briefly described here. Data were collected in two phases.…”
Section: Methodsmentioning
confidence: 99%
“…As such, children with subthreshold symptoms such as symptoms that occur in only one setting or a symptom profile limited to five rather than six symptoms of ADHD are not included. In contrast, Healey, Gopin, Grossman, Campbell, and Halperin (2010) studied children who did not meet full DSM ( DSM-IV ; American Psychiatric Association [APA], 1994) criteria for ADHD, rather had at least six symptoms across settings. Nonetheless, children in their sample had functional impairments, supporting a broader classification approach.…”
Section: Introductionmentioning
confidence: 99%
“…We further hypothesized that both TBI groups would demonstrate a decline in warm responsiveness over time and, conversely, an increase in negativity over time relative to an age-matched cohort of children with OI, again with the expectation of more pronounced differences following a severe TBI. Research involving parent–child interactions has demonstrated that the parent–child relationship experiences more stress in a structured as opposed to a nonstructured task (Healey, Gopin, Grossman, Campbell, & Halperin, 2010; Wade et al, 2008; Barkley, Karlsson, & Pollard, 1985). Hence, we also anticipated that maternal warm responsiveness would be lower in the teaching task.…”
mentioning
confidence: 99%